(untitled) (Revista Contexto & Saúde, 2024)
Objective: To describe social participation and assess its correlation with sensorimotor impairment and functional independence in patients after a stroke in a region of Northeast Brazil. Methods: A cross-sectional study was conducted with 34 stroke patients, aged 18 years or older, selected for convenience from the institution’s health records. Participants were assessed using the following clinical instruments: Assessment of Life Habits 3.1 (LIFE-H 3.1), Functional Independence Measure (FIM), Fugl-Meyer Assessment (FMA) – motor subsection (upper limb-UL and lower limb-LL), and Nottingham Sensory Assessment (NSA). Results: Post-stroke patients exhibited reduced social participation (LIFE-H 3.1), with moderate positive correlations observed between the personal, mobility, and responsibility domains and the total scores of FIM, FIM motor, FMA-motor, and FMA-UL. There was a moderate positive correlation between the total scores of LIFE-H 3.1, FIM, FMA-motor, and FMA-UL. Conclusion: The present study demonstrated a critical loss of social participation in post-stroke subjects, likely attributed to various sensorimotor and functional aspects, in a semi-arid region of Northeast Brazil.